Pemikiran Teologi Sufistik Syaikh Al-Akbar Ibn ‘Arabî - Mutawalli Mutawalli (Universitas Islam Negeri Mataram, 2010)
In any discourse of religion, the existence of God is central because God is the ultimate Being, from whom all creatures come to exist. However, religious perceptions of God have never been unified. In Islam, especially Sufis believe that God is present in all creatures because they are regarded to be the manifestation of God. This stance leads to a divinely-dominated view. This Sufi perception deviates from the maintream thought of Muslim who reject such a view since it reflects pantheism. As the view is common in Sufism, Ibn Arabi, one of the greates Sufi, holds the similar view and introduces a new concept of wahdat al-wujûd. This essay examines the conceptual framework of Ibn Arabi’s Sufi theology and reveals his epistemology. It begins by tracing Ibn Arabi’s socio-intellectual background. It then proceeds to explain his method and view of the union of existence and the concept of God.